Palladium‐SCS Pincer Complexes as Cross‐Linking Moieties in Self‐Healing Metallopolymers. Issue 22 (6th September 2018) - Götz, Stefan; Geitner, Robert; Abend, Marcus; Siegmann, Michael; Zechel, Stefan; Vitz, Jürgen; Gräfe, Stefanie; Schmitt, Michael; Popp, Jürgen; Hager, Martin D.; Schubert, Ulrich S.
Abstract: Metallopolymers combine properties of metal complexes and polymers and are thus interesting materials for a wide field of different applications. One current major field is the utilization as self‐healing polymers, and for this purpose, palladium‐SCS pincer complexes are synthesized. Well‐defined copolymers featuring those metal complexes in the side chain are obtained using the reversible addition–fragmentation chain‐transfer polymerization technique. By the addition of a tetravalent pyridine cross‐linkers, reversible cross‐linked supramolecular networks are prepared, enabling self‐healing properties. By utilizing density functional theory calculations, IR, and Raman spectroscopy, as well as isothermal titration calorimetry, the complex formation, reversibility, and stability are studied. The information of these experiments also enables further optimizations for the design of similar reversible systems in the future. Abstract : Palladium‐SCS pincer complexes are well‐investigated metal–ligand interaction systems applied in the fields of catalysis, sensors, and self‐assembly. Due to their square‐planar binding geometry, they enable the design of defined molecular structures using the fourth binding position of the palladium center. Embedded in polymer matrices, these complexes are applied as reversible cross‐linking moieties, enabling the healing of mechanical damage.